Transplantace jater u pacientů s trombózou v. portae - Janoušek, Libor; Adamec, Miloš; Oliverius, Martin; Trunečka, Pavel; Kučera, Miloš (Časopis lékařů českých, 2011)
Portal vein thrombosis has (PVT) long been an absolute contraindication to liver transplantation. In patients scheduled for liver transplantation, portal vein thrombosis occurs in 4-15%. METHODS AND RESULTS: The authors retrospectively collected data on 740 patients who underwent an initial orthotopic liver transplant at the authors' institution between 1996 and 2009. Mean follow-up was from 1 day to 6 years. There were 437 male patients and 303 female patients. We have performed this procedure in 57 recipients with PVT; this constitutes 7.7% of the overall transplant population. There was a 10.5% incidence of liver graft dysfunction, 10.5% of hepatic artery thrombosis, 19.3% of acute rejection and 17.5% of biliary complications. The overall incidence of relaparotomy for bleeding was 28% (16 patients). In-hospital mortality and late mortality were 15.8% and 31.6%, respectively. Volumes transfused were 17.1 (0-425) transfusion units of red blood cell, 27.1 (0-132) of fresh-frozen plasma and 2.6 (0-20) of platelets respectively. CONCLUSIONS: We confirm that PVT is not a contraindication to LTx at the present time.
Keywords: Female; lidé středního věku; Adolescent; mužské pohlaví; mladý dospělý; žilní trombóza; Humans; dospělí; selhání jater; Venous Thrombosis; Reoperation; lidé; Liver Failure; Middle Aged; transplantace jater; senioři; ženské pohlaví; reoperace; Child; vena portae; Aged; Young Adult; dítě; Adult; Liver Transplantation; Portal Vein; Male; mladiství